STRATEGI BERTAHAN HIDUP KELUARGA PEDAGANG ROTI KELILING DALAM MEMENUHI KEBUTUHAN POKOK DITENGAH PANDEMI COVID-19 (STUDI KASUS DI PABRIK ROTI DS BAKERY, GG. FAMILY, TJ. SARI, KECAMATAN MEDAN TUNTUNGAN) - Fikry Harnas (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Currently, the entire world is being affected by an illness known as Covid-19, which has spread to many parts of the globe and has been declared a pandemic by the World Health Organization. The epidemic has had a wide range of effects in Indonesia's metropolitan areas, including the city of Medan's trade sector. A traveling baker is one of the traders we frequently encounter in Medan. The mobile baker at the DS Bakery bakery is one of the community groups affected by the pandemic, which has resulted in a fall in turnover or income, leaving them impoverished and requiring specific ways to cover their basic requirements, such as clothing, food, So that they can live, they need to be on boards. The goal of this research is to gain a better understanding of the poverty that traveling bakers face and how they cope with it. The principal informant in this study was the owner of the DS Bakery bread factory, from which the traders ordered their bread, and additional informants were two bakery customers. Literature review, observation, interviews, and documentation were all used in the data collection process. The data collected in the field is then qualitatively examined to arrive at findings. The findings of this study also show how this struggling family of traveling bakers can maintain their family's survival by employing active strategies such as maximizing family resources, passive strategies such as minimizing expenses, and network strategies such as leveraging their social connections.